2021
DOI: 10.1080/0886022x.2021.1879852
|View full text |Cite
|
Sign up to set email alerts
|

Hematuria was a high risk for renal progression and ESRD in immunoglobulin a nephropathy: a systematic review and meta-analysis

Abstract: Background: The relationship between hematuria, a typical presentation of immunoglobulin A nephropathy (IgAN), and long-term adverse prognosis of these patients is still controversial. This meta-analysis aims to clarify the effect of hematuria on renal outcomes in IgAN. Methods: Observational cohort studies reporting associations between various forms of hematuria and renal outcomes among IgAN patients were identified from the PubMed and Embase databases. The pooled adjusted risk ratios (RRs) were computed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Although hematuria is a typical presentation of IgAN, its long-term prognostic value remains under debate. A recently published meta-analysis of 7 studies investigated the association between hematuria (binary variable) and ESKD [ 35 ]. They reported that initial hematuria was not associated with a significant increase in the risk of ESKD [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hematuria is a typical presentation of IgAN, its long-term prognostic value remains under debate. A recently published meta-analysis of 7 studies investigated the association between hematuria (binary variable) and ESKD [ 35 ]. They reported that initial hematuria was not associated with a significant increase in the risk of ESKD [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta-analysis of 7 studies investigated the association between hematuria (binary variable) and ESKD [ 35 ]. They reported that initial hematuria was not associated with a significant increase in the risk of ESKD [ 35 ]. Of note, the average age of patients ranged from 30 to 45 in the meta-analysis, which may explain the discrepancy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant interaction between Frontiers in Pharmacology frontiersin.org remission of proteinuria and remission of hematuria in the 6 months prior to treatment. A meta-analysis of 5,660 IgAN patients from 13 literatures (He et al, 2021) concluded that initial microscopic hematuria and persistent hematuria may be associated with renal progression and ESRD. A Kuwaiti study of 69 IgAN patients (Ghani et al, 2011) showed that renal function deterioration was more significant during follow-up (mean followup 3.5 years) in the presence of gross hematuria at biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more scholars called on clinicians to pay attention to the influence of hematuria on IgAN. Both prospective clinical cohort studies (Yu et al, 2020) and metaanalysis (He et al, 2021) proved that hematuria was one of the risk factors for progression of IgAN, and both the degree and duration of hematuria affected the prognosis of the disease (Yu et al, 2020). Compared with patients with mild or negative hematuria, the others with persistent hematuria will more easily develop into ESRD over time.…”
Section: Introductionmentioning
confidence: 99%
“…3 A meta-analysis from 13 studies with 5660 participants reported that baseline microscopic haematuria was associated with an 87% increase in the risk of kidney failure. 4 In STOP-IgAN trial which compared intensive supportive care with and without immunosuppressive therapy in patients with IgAN and proteinuria >0.75 g/day and/or impaired kidney function (eGFR <90 mL/min/1.73 m 2 ), disappearance of microscopic haematuria determined by dipstick or urinary sediment analysis was assessed as a secondary endpoint. 5 Haematuria remission was significantly greater in the immunosuppressive group compared to the supportive care group (42% vs. 16%, respectively; OR 3.73 [95% CI, 1.52-9.14]; p = .004).…”
mentioning
confidence: 99%